Implementasi Konsep “Sinergi” pada Interior Pusat Konservasi Flora Endemik Indonesia di Ungaran, Jawa Tengah - Karunika Muthya Dewi Prabhaswari; Ronald Hasudungan Irianto Sitindjak; Hendy Mulyono (Intra, 2019)
Indonesia has a lot of biodiversity, especially its floral diversity, which habitat is native / endemic in Indonesia which are used as an identity emblem across various regions in Indonesia. However, some of Indonesia's endemic floral are currently endangered to extinction by the conversion of forests to human settlements. The city of Semarang is currently active to improve the tourism sector. One of them is a plan to build a rare plant conservation site. With the enthusiasm of the government, it is expected that people can participate in preserving Indonesian's endemic floral population. Therefore, it is necessary to have a platform that can invite people to take part in preserving floral in Indonesia as well as having a positive impact on botanists and researchers. For this reason, designer presents the Indonesian’s Endemic Floral Conservation Center in Ungaran, Central Java where there are values of conservation, education and recreation. Conservation value is applied to facilities for botanists and researchers for plant breeding. The education and recreation values are applied to facilities for public with the help of technology. Designer raised the concept of "Synergy" by applying an eco-interior approach that gives attention to the reciprocal relationship between humans and nature. The designer expect that with this concept, visitors can be educated by existing facilities and moved to preserve Indonesia's endemic floral.